Mark Twain as Critic - Krause, Sydney J. (Johns Hopkins University Press, 2019)
Originally published in 1967. Mark Twain's literary criticism is a significant branch of his writing that is relatively less explored and appreciated than his other writing. Sydney Krause analyzes the full range of Twain's criticism, much of which has lain neglected in notebooks, letters, marginalia, and autobiographical dictations. This body of work demonstrates that, in addition to being an acute critic given to close reading, Twain thought enough of his criticism to present much of it in an enveloping literary form. In his early criticism Twain used the mask of an ignorant fool (or Muggins), while in his later criticism he used the mask of a world-weary malcontent (or Grumbler). The resulting cross fire from extremes of innocence and experience proved effective against a wide range of literary targets. The Muggins dealt mainly with theater, journalism, oratory, and popular poetry; the grumbler with such writers as Goldsmith, Cooper, Scott, and Hare. Much of this criticism was an outgrowth of Twain's romanticism and therefore has importance for the history of American realism. Mark Twain's criticism was not wholly depreciatory, however. He liked Macaulay, Howells, Howe, Zola, and Wilbrandt, for example, because he found in some of their works the realization of history as an immediate presence. The evidence presented in this book challenges the view that Twain was not a serious student of the craft of writing; he possessed the combination of sensitivity and judgment that all great critics have.